DAMPAK GREEN INTELECTUAL CAPITAL DISCLOSURE TERHADAP SUSTAINABLE BUSINESS DAN KINERJA NON KEUANGAN - Saraswati, Erwin; Inata, Lia Candra (APSSAI ACCOUNTING REVIEW, 2021)
This study aims to examine the components of green intellectual capital (realtional capital, human capital and structural capital) on sustainable business and non-financial performance. Samples obtained by 48 mining companies in Indonesia for two periods, 2017-2018, were tested using simple regression analysis. The results show that green human capital and green structural capital cannot increase a sustainable business. Generally speaking, green intellectual capital can improve financial performance (number of awards received). This research shows that the relationship between the company and stakeholders is not supported through a collaborative approach. The results of this study support the legitimacy theory, mining companies make disclosures that their stakeholders want to legitimize their sustainability.